Quadruple-negative RT-PCR assay for COVID-19, but clinically and radiologically COVID pneumonia with POTS: Case report and case-based review. (December 2021) - Rajendran, Nithya; Rameli, Puteri Maisarah; Collins, Grace
A 25-year-old woman with a background history of bronchial asthma and intellectual disability presented to hospital with progressively worsening dyspnoea. Despite testing negative four times for coronavirus disease infection by nasopharyngeal swab reverse-transcriptase polymerase chain reaction, her clinical symptoms of hypoxaemic respiratory failure and radiological findings on computed tomography pulmonary angiogram were consistent with coronavirus disease pneumonia. Although she made a quick recovery in the intensive care unit with a combination of empirical antibiotics, corticosteroids, high flow nasal oxygen, therapeutic anticoagulation and awake semi proning, her protracted hospital course due to persistent sinus tachycardia remained challenging. A diagnosis of potential postural orthostatic tachycardia syndrome was explored during the acute phase of illness following an active stand test and exclusion of other causes. She was treated with beta blockers as she failed to improve with non-pharmacological measures. We searched for similar cases by analysing the literature databases. Our case aims to stress the importance of recognising and treating patients with negative nasal reverse-transcriptase polymerase chain reaction swabs as coronavirus disease infection, especially if there is strong evidence of clinical and radiological findings where diagnosis is often under recognised in asthmatics with intellectual disability.